Employees Perception towards the implementation of Corporate Governance Principles: An Egyptian Perspective (Global Journal of Human-Social Science, 2017)
The objective of this study is to examine how employees perceive corporate governance in their organisations and to explore the position that employees can take in the promotion of corporate governance in the Egyptian context It empirically examines the employees perception towards corporate governance using a 5-point Likert-type questionnaire that was administered face to face and online Despite the fact that some employees lack proper knowledge about the issues of corporate governance the findings were encouraging as the majority of employees have emphasised its importance The results of this study can be beneficial in developing a better understanding about corporate governance within different Egyptian institutions and in promoting the importance that employees can play in implementing governance